HRCT Spectrum in Initially COVID-19 RT-PCR Negative Patients - Aniqua Saleem; Lubna Meraj; Hira Saleem; Sharjeel Sarfraz Ahmed Sheikh; Sidra Hamid; Huzaifa Saleem (Journal of Rawalpindi Medical College, 2021)
Objective: To analyze radiological spectrum of HRCT in COVID-19 patients, clinically symptomatic but initially having negative RT-PCR.